METHODOLOGY FOR STUDYING MODERN METHODS OF ORGANIZING INDEPENDENT WORK OF STUDENTS IN INORGANIC CHEMISTRY IN HIGHER EDUCATIONAL INSTITUTIONS (Web of Teachers: Inderscience Research, 2026)
This article discusses the methodology for using interactive methods and graphic organizers in organizing independent work of students in inorganic chemistry in higher pedagogical educational institutions. The impact of such methods as “FSMU”, “Insert”, “Charkhpalak”, “Cluster”, “BBB” on the effectiveness of independent learning is analyzed. The results of the study showed that interactive methods develop students' skills of independent thinking, analysis and deep assimilation of knowledge.